Morphological structure and ethnic background of the Sudanese Shagia tribe (East Africa) - Stangret, Anna; Łaba, Alicja; Kempinska-Podhorodecka, Agnieszka (Anthropological Review, 2024)
North Sudan, especially the 4th Nile Cataract region, is home to one of the world’s most isolated human populations. This study aimed to clarify the ethnic background of the Shagia based on anthropological analyses. This study provides a morphological and ethnographic characterisation of the previously unstudied Shagia tribe. Head and body measurements were conducted among 64 adults from three villages. There were observable but relatively small admixture proportions of non-African population genes (light skin colour, narrow noses and masculine proportions) in their morphological build. The Shagia’s uniqueness may have been the result of severe genetic drift episodes resulting from founding events, such as long-term isolation and traditionally small population size. It is useful to trace the ethnic history of Africans and, specifically, for the tribal members of Shagia so that they may better understand and learn about their history. This study shows that the Shagia tribe was displaced from their territory due to the construction of the Merowe Dam. Thus, the results of this research fulfil the assumptions of urgent anthropology, as it contributes to the protection of the heritage of the 4th Nile Cataract region: an area of historical value to the study of the evolution of contemporary civilisation.